The Somatotropic Axis in the Sleep Apnea-Obesity Comorbid Duo - Galerneau, Louis-Marie; Borel, Anne-Laure; Chabre, Olivier; Sapene, Marc; Stach, Bruno; Girey-Rannaud, Janie; Tamisier, Renaud; Pépin, Jean-Louis; Caron, Philippe (Frontiers in Endocrinology, 2020)
Background: Growth hormone (GH) stimulates the production of insulin-like growth factor 1 (IGF-1) in most tissues and together GH and IGF-1 profoundly impact adipose tissue deposition, glucose metabolism and cardiovascular function. A low serum IGF-I level has been reported as being associated with obstructive sleep apnea (OSA) and might be one of the mechanisms underlying cardio-metabolic risk in OSA patients. Methods: In a multicenter national study, 817 patients consulting for suspicion of OSA (OSA confirmed for 567 patients) underwent serum IGF-1 measurements. We analyzed the association between an IGF-1 level below the median value of the population and variables related to cardio-metabolic risk: body mass index (BMI) and waist circumference, apnea hypopnea index (AHI), cholesterol and triglycerides (expressed as median and divided into quartiles for continuous variables). Results: After adjustment for age and gender, low IGF-1 levels were associated with increased BMI and AHI (Odds ratios (OR) = 2.83; p <0.0001 and OR = 3.03, p <0.0001 for Quartile 4 versus Quartile1, respectively), with elevated cholesterol levels (OR = 1.36, p = 0.0444), and elevated triglyceride levels (OR = 1.36; p = 0.0008). Conclusions: Both adiposity and sleep apnea synergistically predict low levels of IGF-1 and thus could together contribute towards cardio-metabolic risk. Further work are needed to confirm whether IGF-1 levels allow grading severity and predicting response to treatments to aim at a personalized medicine for patients suffering from OSA.